2020
DOI: 10.1021/acs.jced.0c00166
|View full text |Cite
|
Sign up to set email alerts
|

Solubility Behavior and Thermodynamic Analysis of Bisphenol A in 14 Different Pure Solvents

Abstract: The solubility of bisphenol A in 14 different pure solvents (N,N-dimethylformamide, formamide, acetone, 1,4dioxane, cyclohexanone, ethyl acetate, methyl acetate, acetonitrile, ethanol, methanol, 1-propanol, 1-butanol, 2-propanol, and 2butanol) was measured at T = (273.15−313.15) K under atmospheric pressure using a laser dynamic method. The experimental data of bisphenol A were correlated by modified Apelblat equation, λh equation, nonrandom two-liquid model and Wilson model, and the fitting results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…The λ h equation , was expressed as where λ and h are the model correlated parameters; the corresponding fitting values are listed in Table . T m is the melting temperature of the solute; the value is 430.83 K …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The λ h equation , was expressed as where λ and h are the model correlated parameters; the corresponding fitting values are listed in Table . T m is the melting temperature of the solute; the value is 430.83 K …”
Section: Resultsmentioning
confidence: 99%
“…In addition, the solubility of benzoic acid in toluene was also measured to further verify the reliability of the experimental device. The literature data , and experimental solubility data curves are presented in Figure a,b, and the comparative data are shown in Tables and . The experimental value agreed well with the literature value, which indicated that the experimental method and device were reliable.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The degradation of the substrate initiated the removal of the toxic, hazard monomer from the CD-BPA-producing an eco-friendly, clean recycling treatment for the upcycling process (Supplementary Fig. 5) 28,29 . The metal from the CD was easily harvested with polyimide (PI) tape, which also serves as the substrate layer in the new device integration to improve the mechanical durability and robustness of the thin metal film (Fig.…”
Section: Main Text [Insert Figure 1]mentioning
confidence: 99%